2014
DOI: 10.1371/journal.pone.0088400
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of the Renal Stroma Defines Its Critical Role in Nephron Progenitor and Vasculature Patterning

Abstract: The renal stroma is an embryonic cell population located in the cortex that provides a structural framework as well as a source of endothelial progenitors for the developing kidney. The exact role of the renal stroma in normal kidney development hasn't been clearly defined. However, previous studies have shown that the genetic deletion of Foxd1, a renal stroma specific gene, leads to severe kidney malformations confirming the importance of stroma in normal kidney development. This study further investigates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
91
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 19 publications
9
91
0
Order By: Relevance
“…Recently, a stromaless kidney ( produced by expression of diphtheria toxin in the Foxd1 lineage) was shown to phenocopy Fat4 nulls (Das et al, 2013;Hum et al, 2014). Owing to complete removal of the stromal compartment, the authors were unable to determine if a single molecular factor was responsible for the increased CM observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a stromaless kidney ( produced by expression of diphtheria toxin in the Foxd1 lineage) was shown to phenocopy Fat4 nulls (Das et al, 2013;Hum et al, 2014). Owing to complete removal of the stromal compartment, the authors were unable to determine if a single molecular factor was responsible for the increased CM observed.…”
Section: Discussionmentioning
confidence: 99%
“…Stromal cells regulate both UB renal branching and the balance between self-renewal and nephron differentiation of the CM (Batourina et al, 2001;Das et al, 2013;Hatini et al, 1996;Hum et al, 2014;Levinson et al, 2005;Mendelsohn et al, 1999Mendelsohn et al, , 1994Paroly et al, 2013). Loss of the stromal transcription factor gene Foxd1 results in reduced branching and an expanded CM (Hatini et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…2A-D). Increased thickness and disorganization of CM has also been noted in kidneys with stromal deletion, or mutation of Ecm1, Foxd1 or Fat4 (Das et al, 2013;Hatini et al, 1996;Hum et al, 2014;Levinson et al, 2005;Paroly et al, 2013).…”
Section: Influence Of Dchs1 On CMmentioning
confidence: 95%
“…The CM is surrounded by stroma. Genetic ablation of stromal cells or mutation of stromal-expressed genes, including Ecm1, Foxd1 and Fat4, has revealed that stroma influences the development of the CM and UB (Das et al, 2013;Hatini et al, 1996;Hum et al, 2014;Levinson et al, 2005;Paroly et al, 2013). Nonetheless, there remain substantial gaps in our understanding of the cellular and molecular mechanisms that orchestrate the communication between stromal cells and other cell layers required for kidney morphogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation